Investigation of hgse films, deposited from aqueous solutions with different complexing agents - Chaykivska, Ruslana; Sozanskyi, Martyn; Stadnik, Vitalii; Guminilovych, Ruslana; Shapoval, Pavlo; Yatchyshyn, Yosyp (Видавництво Львівської політехніки, 2017)
The process of synthesis of mercury selenide (HgSe) thin films by a chemical bath deposition method (CBD) with using different complexing agents (potassium rodanide, potassium iodide and sodium thiosulfate) has been investigated. The phase composition, crystal structure, absorption spectra, surface morphology of HgSe films were studied. The effect of nature of complexing agent on the properties of obtaining coatings was shown. The HgSe films have a sphalerite structure, nearly stoichiometric atomic ratios of mercury to selenium and optical band gaps, which are localized in the ranges 1.38-2.40 eV, depending on the usage of complexing agent.
Keywords: mercury selenide; semiconductor films; chemical bath deposition; optical band gap; structure and morphology of thin films